SISTEM PENGENDALIAN INTERNAL PIUTANG DALAM MEMINIMALKAN PIUTANG TAK TERTAGIH PADA PT PCS - Dewi Safitri Dewi; Wasti Reviandani (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The payment system used by PT PCS can generally be done in cash or credit, the increase in credit sales is an inhibiting factor in increasing company profits, because many customers are late in paying receivables until they exceed the payment due date. This problem occurs because there is no effective accounts receivable control system at PT PCS. This study aims to analyze the accounts receivable internal control system in minimizing bad debts at PT PCS. The method used is descriptive qualitative method to describe the representation of internal control and bad debts at PT PCS through interviews and observations. The results obtained by researchers are, PT PCS has not implemented a good accounts receivable internal control system, as evidenced by the large number of PT PCS employees who collect accounts receivable without paying attention to the terms and conditions in accordance with the Standard Operating Procedure for credit sales applicable at PT PCS, and based on the calculation of the accounts receivable collection ratio, proving that uncollectible accounts at PT PCS from 2018 to 2022 have increased significantly.